Evaluation of Sports Learning Methods of SD IT Haudhin Ilma Langkat City - Suyono, Suyono; Prisila, Rizki; Al Farisi, Muhammad; Ginting, Herdika Fauzan (ALACRITY : Journal of Education, 2024)
Physical education and sports (PES) play a crucial role in the holistic development of individuals, particularly in physical, mental, and social health. Primary schools (SD) serve as an ideal setting for instilling healthy and active lifestyles through effective sports education. At SD IT Haudhin Ilma Kota Langkat, serious attention is given to this aspect. Therefore, an evaluation of the sports education methods employed in the school is essential to ensure the achievement of desired physical education goals. This study employs a qualitative method with an observational analysis approach to assess the sports education process at SD IT Haudhin Ilma Kota Langkat. The research aims to provide a deeper understanding of the effectiveness of sports education methods applied at SD IT Haudhin Ilma Kota Langkat. Consequently, it is anticipated that this study will contribute positively to the development and enhancement of sports education processes at the primary school level.